Identification of active oxalotrophic bacteria by Bromodeoxyuridine DNA labeling in a microcosm soil experiments. Issue 2 (23rd September 2013) - Bravo, Daniel; Martin, Gaëtan; David, Maude M.; Cailleau, Guillaume; Verrecchia, Eric; Junier, Pilar
Abstract: The oxalate–carbonate pathway (OCP) leads to a potential carbon sink in terrestrial environments. This process is linked to the activity of oxalotrophic bacteria. Although isolation and molecular characterizations are used to study oxalotrophic bacteria, these approaches do not give information on the active oxalotrophs present in soil undergoing the OCP. The aim of this study was to assess the diversity of active oxalotrophic bacteria in soil microcosms using the Bromodeoxyuridine (BrdU) DNA labeling technique. Soil was collected near an oxalogenic tree ( Milicia excelsa ). Different concentrations of calcium oxalate (0.5%, 1%, and 4% w/w) were added to the soil microcosms and compared with an untreated control. After 12 days of incubation, a maximal pH of 7.7 was measured for microcosms with oxalate (initial pH 6.4). At this time point, a DGGE profile of the frc gene was performed from BrdU‐labeled soil DNA and unlabeled soil DNA. Actinobacteria ( Streptomyces‐ and Kribbella ‐like sequences), Gammaproteobacteria and Betaproteobacteria were found as the main active oxalotrophic bacterial groups. This study highlights the relevance of Actinobacteria as members of the active bacterial community and the identification of novel uncultured oxalotrophic groups (i.e. Kribbella ) active in soils.